Social Shopping Motivations of Impulsive and Compulsive Buying Behaviors - Moin Ahmad Moon; Amna Farooq; Maira Kiran (UW Journal of Management Sciences, 2022)
Purpose: The study aimed to examine the causal relationship between social influences and impulsive buying behavior & compulsive buying behavior in context of fashion shopping. Methodology/Design: Questionnaire was administered to 372 young consumers. A structural equation model using AMOS 22 was analyzed utilizing maximum likelihood method. Findings: Informational influences, normative influences, and risk towards fashion, social comparison orientation and social shopping motivations had significant relationship with impulsive buying. Social risk towards fashion did not encourage social shopping motivation and social shopping motivations proved to be significant predictor of impulsive and compulsive buying. Originality/Value: Study is amongst the very first to investigate social influences of impulsive and compulsive buying behavior in a developing economy. Implication: Theoretical and practical implications are discussed along with future recommendations. Limitations: This study was limited to university students of one city of Pakistan and to fashion products..